2019
DOI: 10.3389/fncel.2019.00402
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Characterization of Gut Microbiota-Derived Bacterial Strains With Neuroprotective Properties

Abstract: Neurodegenerative diseases are disabling, incurable, and progressive conditions characterized by neuronal loss and decreased cognitive function. Changes in gut microbiome composition have been linked to a number of neurodegenerative diseases, indicating a role for the gut-brain axis. Here, we show how specific gut-derived bacterial strains can modulate neuroinflammatory and neurodegenerative processes in vitro through the production of specific metabolites and discuss the potential therapeutic implications for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 66 publications
(70 reference statements)
0
37
0
Order By: Relevance
“…This confirmed previous study performed in gnotobiotic mice colonized with P. distasonis showing an induction of Treg differentiation [ 84 ]. A strain of P. distasonis was shown to reduce neuroinflammation in vitro by exhibiting a strong capacity to reduce IL-6 secretion, but also antioxidant capacity on different brain cell lines [ 85 ]. All these results highlight the potential anti-inflammatory effect of this bacterium at multiple levels and its ability to promote intestinal barrier integrity, as we observed in our models.…”
Section: Discussionmentioning
confidence: 99%
“…This confirmed previous study performed in gnotobiotic mice colonized with P. distasonis showing an induction of Treg differentiation [ 84 ]. A strain of P. distasonis was shown to reduce neuroinflammation in vitro by exhibiting a strong capacity to reduce IL-6 secretion, but also antioxidant capacity on different brain cell lines [ 85 ]. All these results highlight the potential anti-inflammatory effect of this bacterium at multiple levels and its ability to promote intestinal barrier integrity, as we observed in our models.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported reduction of the Parabacteroides in multiple sclerosis patients where its exerts a protective role by stimulating anti-inflammatory IL-10–expressing human CD4 + CD25 + T cells [ 81 ]. In a study assessing the neuroprotective ability of fifty gut bacterial strains, Parabacteroides distasonis had the strongest capacity to reduce IL-6, with a potential to be used as a live biotherapeutic in disorders characterized by neurodegeneration and neuroinflammation [ 82 ]. Oral administration of Parabacteroides components (mPd) is known to be effective in dampening the production of proinflammatory cytokines via innate and adaptive immunomodulatory mechanisms [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…This, just to remain with the neuroblastoma example, are also of relevance in other cancer progression or even in neurophysiology. Accordingly, gut microbiota shows neuroprotective properties, reducing IL-6 secretion in different neural cell lines, including neuroblastoma [ 84 , 85 ]. Here, these investigators identified two specific strains, Parabacteroides distasonis MRx0005 and Megasphaera massiliensis MRx0029, producing distinct C1-C3 or C4-C6 fatty acids [ 84 ] or, in another context, galacto-oligosaccharides [ 86 ] or short-chain fatty acid receptor 3 [ 87 ].…”
Section: Is There a Role For Exogenous Factors Such As Microbiome?mentioning
confidence: 99%
“…Accordingly, gut microbiota shows neuroprotective properties, reducing IL-6 secretion in different neural cell lines, including neuroblastoma [ 84 , 85 ]. Here, these investigators identified two specific strains, Parabacteroides distasonis MRx0005 and Megasphaera massiliensis MRx0029, producing distinct C1-C3 or C4-C6 fatty acids [ 84 ] or, in another context, galacto-oligosaccharides [ 86 ] or short-chain fatty acid receptor 3 [ 87 ]. Similarly, Roseovarius albus increases brain derived neurotropic factor (BDNF) expression while reducing Bax/Bcl-2 ratio in neuroblastoma cell lines [ 88 ].…”
Section: Is There a Role For Exogenous Factors Such As Microbiome?mentioning
confidence: 99%